Standardized approach for evaluating tumor infiltrating lymphocytes in canine mammary carcinoma: Spatial distribution and score as relevant features of tumor malignancy. (May 2022) - Muscatello, L.V.; Avallone, G.; Brunetti, B.; Bacci, B.; Foschini, M.P.; Sarli, G.
Abstract: Neoplastic cells, through immunoediting mechanisms, can establish a state of immunosuppression to evade host immune defenses. The aims of this study were: (1) to validate a standard method for assessing tumor infiltrating lymphocytes (TILs) in canine mammary carcinoma by applying international human breast cancer guidelines; (2) to investigate if the TILs population was composed of a subset of regulatory T lymphocytes (Tregs); and (3) to evaluate the relationship between the number of TILs and Tregs and the biological behavior of the tumors. One hundred and twenty-nine canine mammary tumors were retrospectively selected for this study. Histological diagnosis, grading and histological evaluation of TILs was performed on hematoxylin and eosin-stained sections. TILs were evaluated using a three-tier semiquantitative method, previously validated in human medicine, based on the percentage of TILs (0–10%, 11–40% and 41–90%). Lymphocyte immunophenotype was confirmed by CD3 and CD79, while an anti-FoxP3 antibody was used to determine the presence of Tregs. The number of stromal TILs and invasive front TILs significantly correlated with each other ( P < 0.0001) and increased with increasing histological grade ( P = 0.002 and P = 0.004, respectively). A subset of TILs was composed of FOXP3 + Tregs. Stromal Tregs and invasive front Tregs were associated with stromal TILs and invasive front TILs ( P = 0.03; P = 0.01 and P = 0.003; P = 0.007, respectively). In conclusion, in canine mammary carcinomas, an increased number of stromal and invasive front TILs is associated with increased malignancy and significant increase of Tregs that could lead to immunosuppression and evasion of the host immune system. Highlights: Tumor infiltrating lymphocytes (TILs) in canine mammary carcinoma were assessed. Stromal and invasive front TILs increased with increased malignancy. TIL infiltration was positively associated with the number of regulatory T cells.